POLITE LANGUAGE OF COMMUNICATIVE COMPETENCY MODEL - Tri Widiatmi, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
This paper is a preliminary study in the attempt of developing a polite communicative competency model. This module is used in learning practice in the class to improve the students’ communicative potency. Considering this, this paper is divided into two sections. Firstly, this paper aims to describe theory, relevant previous studies, and framework of polite communicative competency in a conversation. The definition of communicative competency and polite language is important to discuss here. Competency concerns the language users’ knowledge and understanding on language norm and its users’ situation context. Using language communicatively is the way of using language according to its function, using language understandable to the listeners. To use polite and impolite languages, the users should consider the aspects of polite language achievement. Diction should be appropriate to the topic, context, circumstance and message delivered. Secondly, this paper explains the type of model that can be used in learning context to motivate and to improve the students’ communicative competency. Communicative method contains communicative design and communicative teaching procedure. In conversation interaction, language ability should be integrated into the aspects of language politeness. Therefore, to improve language ability, an appropriate learning model is required in the attempt of achieving the polite communicative competency among the students.